On Superconductivity and Superfluidity A Scientific Autobiography - Ginzburg, Vitaly L. (Springer Berlin Heidelberg, 2009)
This book presents the Nobel Laureate Vitaly Ginzburg's views on the development in the field of superconductivity. It contains a selection of Ginzburg's key writings, including his amended version of the Nobel lecture in Physics 2003. Also included are an expanded autobiography, which was written for the Nobel Committee, an article entitled "A Scientific Autobiography: An Attempt," a fundamental article co-written with L.D. Landau entitled "To the theory of superconductivity," an expanded review article "Superconductivity and superfluidity (what was done and what was not done)," and some newly written short articles about superconductivity and related subjects. So, in toto, presented here are the personal contributions of Ginzburg, that resulted in the Nobel Prize, in the context of his scientific biography.